Are common mental disorders more prevalent in the UK serving military compared to the general working population?. Issue 9 (July 2015) - Goodwin, L.; Wessely, S.; Hotopf, M.; Jones, M.; Greenberg, N.; Rona, R. J.; Hull, L.; Fear, N. T.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Although the military is considered to be a stressful occupation, there are remarkably few studies that compare the prevalence of common mental disorder (CMD) between the military and the general population. This study examined the prevalence of probable CMD in a serving UK military sample compared to a general population sample of employed individuals. Method Data for the general population was from the 2003 and 2008 collections for the Health Survey for England (HSE) and for the serving military from phases 1 (2004–2006) and 2 (2007–2009) of the King's Centre for Military Health Research (KCMHR) cohort study. Probable CMD was assessed by the General Health Questionnaire (GHQ-12). The datasets were appended to calculate the odds of CMD in the military compared to the general population. Results The odds of probable CMD was approximately double in the military, when comparing phase 1 of the military study to the 2003 HSE [odds ratio (OR) 2.4, 95% confidence interval (CI) 2.1–2.7], and phase 2 to the 2008 HSE (OR 2.3, 95% CI 2.0–2.6) after adjustment for sex, age, social class, education and marital status. Conclusions Serving military personnel are more likely to endorse symptoms of CMD compared to those selected from a general population study as employed in other occupations, even after accounting for demographic characteristics. This difference may be partly explained by the context of the military study, with evidence from previous research for higher reports of symptoms from the GHQ in occupational compared to population studies, in addition to the role of predisposing characteristics.